Dyadic dynamics of perceived social support in couples facing infertility - Martins, Mariana V. (2014)
Is perceived social support from partner, family, and friends associated with increased infertility-related stress? While mens perceived support did not seem to influence their partners stress, womens perceptions of spousal and familial support can affect the way men deal with the challenge of infertility. Previous studies showed that low levels of social support are associated with poor psychosocial adjustment and treatment termination in women and men. Studies examining the impact of social support using the couple as unit of analysis are lacking. A cross-sectional sample of 613 Portuguese patients participated in the research, online over a 3-month period, and in a public fertility clinic over 11 months. The final sample comprised 213 married or cohabiting couples (191 from the fertility clinic) who were actively attempting to have a child, were seeking infertility treatment and had not undergone previous preimplantation genetic diagnosis. Perceived social support was assessed through the Multidimensional Scale of Perceived Social Support and infertility-related stress was assessed with the fertility problem inventory. Hypotheses were tested by applying the actorpartner interdependence model using structural equation modeling. Couples had been living together for an average (SD) of 6 3.5 years, and attempting a pregnancy for 3.8 2.6 years. Nearly half of the couples had undergone infertility treatment (41.3). Infertility stress was found to be associated with low family support for women ( 0.27, P .003), and low partner support for both men ( 0.29, P .001) and women ( 0.45, P .006). Both women and mens perceived friend support were not significantly related to male or female infertility stress. Men infertility stress was also associated with their partners low levels of partner ( 0.24, P .049) and family support ( 0.23, P .001). No significant partner effects were observed for women. Despite being related to actor effects alone (female partner and family support), the explained variance of the model in womens fertility stress was greater (R-2 21) than that (R-2 15.6) for the combined actor and partner effects in mens fertility stress (male partner support, female partner and family support). The study data are cross-sectional and the generalizability of results is limited by self-selection. The characteristics of non-participants in both the clinical and online samples were not available, the perception of infertility-specific supportive behaviors was not assessed and differential analyses according to infertility diagnosis were not included in this study. Our data underline the importance of partner support in alleviating the burden of infertility. Men may experience infertility indirectly through the impact that it has on their partners. Our findings reinforce the need to involve the male partner throughout the whole treatment process and for couple-based interventions when providing infertility counseling. Further prospective research should be aimed at investigating the male experience of infertility. This research was supported by a PhD scholarship from the Portuguese Foundation for Science and Technology granted to M.M. (FCT, SFRH/BD/44232/2008). The authors have no conflicts of interest to declare.